Identifying Gazelles : Expert Panels vs. Surveys as a Means to Identify Firms with Rapid Growth Potential - Fafchamps, Marcel (World Bank, Washington, DC, 2016)
A business plan competition is conducted to test whether survey instruments or panel judges are able to identify the fastest growing firms. Participants submitted six- to eight-page business plans and defended them before a three- or four-judge panel. Applicants are surveyed shortly after they applied and one and two years after the competition. Follow-up surveys are used to construct measures of enterprise growth and baseline surveys and panel scores to construct measures of enterprise growth potential. A survey measure of ability correlates strongly with future growth, but the panel scores add to predictive power even after controlling for ability and other survey variables. The survey questions have more power to explain the variance in growth. Participants presenting before the panel were given a chance to win customized management training. Fourteen months after the training, there is no positive effect of the training on growth of the business.